Acellular dermal matrix in reconstructive surgery: Applications, benefits, and cost - Mohammadyari, Fatemeh; Parvin, Sadaf; Khorvash, Mohsen; Amini, Amirhasan; Behzadi, Amirhossein; HajEbrahimi, Reyhaneh; Kasaei, Fatemeh; Olangian-Tehrani, Sepehr (Frontiers in Transplantation, 2023)
Modern tissue engineering has made substantial advancements that have revolutionized plastic surgery. Acellular dermal matrix (ADM) is an example that has gained considerable attention recently. ADM can be made from humans, bovines, or porcine tissues. ADM acts as a scaffold that incorporates into the recipient tissue. It is gradually infiltrated by fibroblasts and vascularized. Fortunately, many techniques have been used to remove cellular and antigenic components from ADM to minimize immune system rejection. ADM is made of collagen, fibronectin, elastin, laminin, glycosaminoglycans, and hyaluronic acid. It is used in critical wounds (e.g., diabetic wounds) to protect soft tissue and accelerate wound healing. It is also used in implant-based breast reconstruction surgery to improve aesthetic outcomes and reduce capsule contracture risk. ADM has also gained attention in abdominal and chest wall defects. Some studies have shown that ADM is associated with less erosion and infection in abdominal hernias than synthetic meshes. However, its higher cost prevents it from being commonly used in hernia repair. Also, using ADM in tendon repair (e.g., Achilles tendon) has been associated with increased stability and reduced rejection rate. Despite its advantages, ADM might result in complications such as hematoma, seroma, necrosis, and infection. Moreover, ADM is expensive, making it an unsuitable option for many patients. Finally, the literature on ADM is insufficient and more research on the results of ADM usage in surgeries is needed. This article aims to review the literature regarding the application, Benefits, and costs of ADM in reconstructive surgery.